Monitor grazing to manage grazing pressure: The use of GPS tracking collars in the Portuguese silvopastoral Montado – case study - Ferraz-de-Oliveira, M. I. (2020)
Extensive grazing systems are an integrated combination of animals, soils, plants and procedures, used to address animal production in ever changing environments. Within extensive grazing systems livestock spatial distribution is a central issue, both for production and conservation objectives. The Portuguese silvopastoral Montado is a human shaped ecosystem characterized by an open tree canopy of Quercus. rotundfolia and Quercus suber and a diverse undercover of shrubs and grasslands grazed by different livestock species. Livestock production is a dominant activity and one of the most important sources of income to rural communities in Montados. However, to manage such system for maximization of livestock production on a sustainable basis is challenging, as both overgrazing and undergrazing may occur and negatively impact the ecosystem. The concentration of livestock grazing in areas of gentle terrain, near water sources, within riparian galleries and in areas with small young trees often occurs. Conversely, livestock tend to avoid steep slopes bushy areas and areas far from water. The concentration of livestock grazing associated with uneven grazing distribution leads to undergrazed and overgrazed areas across one single paddock. Grazing pressure, considering simultaneously the pasture availability, stocking rates, and the time spent grazing in a given paddock, has been devised as a useful indicator to monitor grazing. Global Navigation Satellite System (GNSS) technology enables livestock tracking and monitoring of position and movements on a 24 hour basis. Tracking data may be used to produce maps of real grazing activity across time. This information can be used to estimate possible number of grazing days based on real paddock utilization rather than potential paddock utilization. Furthermore the identification of preferred grazing areas within a paddock may be used to derive site specific management actions, such as protection of tree regeneration, positioning of water sources or use of electric fencing. In the present ongoing study, we combine monitoring of spatial behaviour of livestock with monitoring of pasture availability. We used 4 GPS collars (Digit Animal) to monitor a herd (48 cattle) movement across a 38ha paddock over the pasture growing season (2018) in Herdade da Mitra, Universidade de Évora (Portugal). Positions (latitude and longitude were collected every 30 minutes and data transmitted via Sigfox low power wide area network. Intensity occupation maps were drawn using the heatmap function of the Google Maps API. Data on pasture biomass availability as well as nutritive value were obtained and the number of grazing days estimated using the protein and energy requirements of the cattle herd as well as its spatial distribution. Cattle behaviour changed in response to pasture decline of nutritive value. Monitoring cattle grazing distribution and pasture biomass and nutritive value can assist producers to better manage grazing intensity and paddock utilisation.